2010
DOI: 10.1590/s0103-50532010000700005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural and spectroscopic studies of novel azo-containing N,O-bonded complexes in the α-Iminoketone and Azophenolate forms

Abstract: Este artigo descreve a síntese e a caracterização espectroscópica e estrutural por difratometria de raios X em monocristal de dois novos complexos contendo o grupamento azo, cis-bis[4-nitro-2-(4-nitrofenilazo)-fenolato-κN 1 ]bis(piridino-κN)cádmio(II), 1, e cis-bis[2-(4-fenilazofenilimino)-2H-acenafteno-1-ona]dicloromercúrio(II), 2. Embora os ligantes e os metais sejam diferentes, observa-se para os dois complexos uma coordenação do tipo N,O-bidentada ao átomo central. Em 1, a coordenação é feita por um átomo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…All complexes reported in this study were obtained as analytically pure solids, confirmed by performing elemental analyses and FTIR spectroscopy. The FTIR spectrum of N1C1 showed a ν(C=N) + ν(C=C) band at 1,586 cm -1 , which was similar to that found in previous studies [29,30]. Additionally, ν(N-H) bands were observed around 3,500 cm -1 , and bands assigned to aromatic C-H vibrations appeared around 3,030 cm -1 .…”
Section: Synthesis Spectroscopy and Dft Calculationssupporting
confidence: 87%
“…All complexes reported in this study were obtained as analytically pure solids, confirmed by performing elemental analyses and FTIR spectroscopy. The FTIR spectrum of N1C1 showed a ν(C=N) + ν(C=C) band at 1,586 cm -1 , which was similar to that found in previous studies [29,30]. Additionally, ν(N-H) bands were observed around 3,500 cm -1 , and bands assigned to aromatic C-H vibrations appeared around 3,030 cm -1 .…”
Section: Synthesis Spectroscopy and Dft Calculationssupporting
confidence: 87%
“…To our surprise, under identical reaction conditions the use of R-BIAN with R = H (Charts and ) selectively results in [ 2 ]­ClO 4 (blue powder) encompassing [ N -(phenyl)­imino]­acenapthenone (BIAO) via the hydrolysis of one of the imine bonds (CNPh → CO) of BIAN. Complex 2 + represents the first example of a ruthenium-coordinated BIAO ligand; the corresponding mercury, cobalt,copper, and zinc complexes were however reported recently. The representative yellow-colored aqua derivative [Ru II (tpm)­(4-OMe-BIAN)­(H 2 O)]­(ClO 4 ) 2 [ 3a ]­(ClO 4 ) 2 (Chart ) has been prepared from the corresponding chloro derivative ([ 1a ]­ClO 4 ) in the presence of excess AgClO 4 in refluxing 1:3 acetone–water via the Cl/H 2 O exchange process. , …”
Section: Resultsmentioning
confidence: 99%
“…In this context, the present report deals with the structurally characterized selective ruthenium complexes of BIAN and the corresponding in situ generated partially hydrolyzed [ N -(phenyl)­imino]­acenapthenone , (BIAO, Scheme ) in combination with tridentate 2,2′:6′,2′′-terpyridine/Cl/H 2 O co-ligands (Scheme ). The primary objective of the article is to address the following aspects: Impact of the “R” group on the electron uptake processes of coordinated BIAN in the light of exploring the feasibility of pushing the electron(s) into the antibonding orbitals of naphthalene, i.e., beyond its α-diimine fragment. Application potential of the complexes toward different catalytic processes. The difference between the BIAN and BIAO derived complexes, if any. …”
Section: Introductionmentioning
confidence: 99%